Кольцо: роман / Даниэла Стил ; перевод с английского Э. Вароновой - Стил Даниэла (АСТ, 2003)
Экземпляры: аб. (20191008) / Инвентарный номер: 59803 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: С 80 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44